Social Cognition in a Clinical Sample of Personality Disorder Patients - Ruiz-Tagle, Amparo; Costanzo, Elsa; De Achával, Delfina; Guinjoan, Salvador (Frontiers in Psychiatry, 2015)
Social cognition was assessed in a clinical sample of Personality Disorder (PD) stable patients receiving ambulatory treatment (N=17) and healthy matched controls (N=17) using tests of recognition of emotions in faces and eyes, in a test of social faux pas and in theory of mind stories. Results indicated that when compared with healthy controls, individuals with PD showed a clear tendency to obtain lower scoring in tasks assessing recognition of emotion in faces (T=-2,602, p=0,014), eyes (T=-3,593, p=0,001), TOM stories (T=-4,706, p=0,000) and Faux pas (T=-2,227, p=0,035). In the present pilot study, PD individuals with a normal cognitive efficiency showed an impaired performance at social cognition assessment including emotion recognition and theory of mind.